Influence of C-reactive protein on the occurrence and assessing of albuminuria severity in diabetics - Lamija Pojskić; Sabaheta Hasić; Ema Tahto; Vildana Arnautović-Torlak; Belma Pojskić; Branka Bedenić (Medicinski glasnik, 2017)
Aim: To asses relation of serum high sensitive C-reactive protein (hsCRP) level with albumin concentration in daily urine in patients with diabetes mellitus type 2 (T2DM). Methods: The prospective study included 69 patients with T2DM, both sexes (24 males, 45 females), aged 30-82 years. They were divided into two groups: patients with T2DM and normoalbuminuria (T2DM-NA; n=40) and patients with T2DM and microalbuminuria (T2DM-MA; n=29). Patients were hospitalized at the Department of Internal Medicine, Cantonal Hospital Zenica, in the period January-April 2014. Immunonephelometry measurement of hsCRP was performed on the Nephelometer Analyzer BN II (Siemens, Germany). Results: Frequency of patients in T2DM-NA and T2DM-MA groups was not significantly different in relation to sex and age. There was significant difference in relation to duration of diabetes ( p=0.001). Average glucose and HbA1c levels were significantly higher in T2DM-NA group comparing to T2DM-MA group (p=0.008 and p=0.047, respectively). Serum creatinine (p=0.011), urea (p=0.009) and hsCRP (p=0.005) were significantly higher in T2DM-MA group compared to T2DM-NA group. Urinary albumin showed significantly positive correlation with the hsCRP (rho=0.286; p=0.017), urea (rho=0.503) and creatinine (rho=0.438) (p<0.0005). A one unit (mg/L) increase in hsCRP concentration was associated with 11.5% increase of odds of microalbuminuria OR=1.115; 95% CI 1.014-1.225; p=0.025). Conclusion: Significantly higher values of serum hsCRP in patients with type 2 diabetes mellitus and microalbuminuria in comparison to those with normoalbuminuria as well as the correlation of values of inflammatory marker with urinary albumin implicate a low grade inflammation in the progression of diabetic nephropathy.
Keywords: diabetic nephropathy; endothelium; inflammation